Construction of 3D Metallic Nanostructures on an Arbitrarily Shaped Substrate. Issue 33 (13th June 2016) - Chen, Fei; Li, Jingning; Yu, Fangfang; Zhao, Di; Wang, Fan; Chen, Yanbin; Peng, Ru‐Wen; Wang, Mu
Abstract : Constructing conductive/magnetic nanowire arrays with 3D features by electrodeposition remains challenging. An unprecedented fabrication approach that allows to construct metallic (cobalt) nanowires on an arbitrarily shaped surface is reported. The spatial separation of nanowires varies from 70 to 3000 nm and the line width changes from 50 to 250 nm depending on growth conditions.